Crossover replantation of a foot after bilateral traumatic lower-leg amputation. (June 2022) - Zhou, Pan; Chen, Zhenbing
Abstract: A successful case of crossover replantation of the left foot to the stump of the right leg was described. The lower extremities were amputated at different levels. On the left side, there was a complete amputation in the distal part of the lower leg with comminuted fracture of the distal tibia. On the right side, there was a complete amputation in the hindfoot with comminuted fracture of both the talus and calcaneus. Since anatomical replantation was impossible, we performed crossover replantation of the left foot to the right lower leg. At the latest follow-up examination, forty-six months after the accident, the patient walked independently with a prosthesis on the stump of the left leg. Crossover replantation should be considered in bilateral amputations for the salvage of at least one extremity.